PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN HUTAN PRODUKSI DI DESA SIGIMPU KECAMATAN PALOLO KABUPATEN SIGI - Nisa, Hairun; Golar, Golar; Arianingsih, Ida (Universitas Tadulako, 2019)
The participation is involvement society as active that is considered as one of the key for the approach that very promise in management forest production in development forest plants program. The government have to eforts the construction forest plants either in the forest area or in area the society property, that is more emphasize for the society participation aspect in it. The research purpose to know the society participation level and the elements relation that influence the society participation for the forest production management in development forest plants program. This research is done for three month begin april until june 2016. The location of research in sigimpu village in palolo subdistrict sigi regency.The method is used in this research, used spearmank rank correlation test. The result of this research that the society participation level for planning phase in development forest plants activity is low while for implementation phase is high. The factors infivence the participation of society for the forest plant development seen by age, education level and income level. The relation between factors influence the participation of society for every phase of development of forest plants activity, that is age factor with every phase of development of forest plants is valueable positive that pointed out of the same direction system, education level is pointed out of the same direction system too. For planning and implementation phase is pointed out of the same direction system, too.